Rhythm control in patients with atrial fibrillation admitted to outpatient clinic. (11th May 2022) - Carvalho, D; Carvalho, P; Ferraz, L; Pacheco, A; Carvalho, S; Ferreira, R; Bastos, JM; Neves, AB
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) is the most common arrhythmia encountered in clinical practice. Patients are often symptomatic leading to a reduction in quality of life. Recent studies suggests that early rhythm control therapy have a clinical benefit in patients with recently diagnosed AF. Purpose: This study aims to evaluate outpatient with AF referred to an outpatient clinic to electrical Cardioversion. Besides that, the study aims to evaluate if outpatient referred from the emergency room had spontaneously reverted to sinus rhythm. Material and Methods: Retrospective observational study carried out through the analysis of the clinical process. Clinical data were collected from AF patients evaluated in an outpatient clinic during the year of 2020. Statistical analysis was made using R software and RStudio. Results: This study included 92 patients evaluated in an outpatient clinic and referred because paroxysmal, persistent and long standing AF to electrical cardioversion. Average age was 67.3 ± 10.1 years. 78 patients had atrial fibrillation and 14 patients had atrial flutter. Hypertension was the most prevalent risk factor (n=83; 79, 3%), followed by dislipidemia (n=66; 71.7%), overweight (n=43; 46, 7%), diabetes mellitus (n=27; 29.3%) and smoke (n=20; 21.7%). 15 patients had paroxysmal AF, 67 patients had persistent AF and 10 patients had long standing AF. CHA2DS2VASC median were 2, 78 ± 1.66 and HASBLED median was 1, 14 ± 0.94. The heart rate control were most frequently made with betablocker (n=78; 84.7%). 4 patients (4, 3%) were medicated with digoxin and 3 patients with calcium channel blockers. 69 patients were forwarded from external consultant and 23 patients from the emergency room (ER). We verified that 12 patients (52, 2%) were in sinus rhythm in admission of outpatient clinic and had spontaneously reversion to sinus rhythm. Mostly patients with paroxysmal AF were from the ER (80% of all patients, p<.001) and mostly patients with persistent and long standing AF were from external consultant (respectively 82% p<0.01 and 85% p<0, 01). Symptoms improvement were evaluated by EHRA classification. Mostly patients had clinical improvement after electrical or spontaneously cardioversion (63%, p.0.02). The median EHRA score previous to CVE were "2" and after cardioversion were "1". Conclusions: Risk factor control is the cornerstone of AF prevention. Control rhythm is important to improve clinical symptons related to AF. However, we can delay cardioversion in a recent acute episode in the emergency room. In our sample, it seems that AF with short natural story presents more in emergency room and the more chronic comes to our consultation.